Fundamentals of Entrepreneurship (ENT300) : WALK Sdn Bhd / Siti Aisyah Ilias - Ilias, Siti Aisyah (2020)
‘WALK’ is the brand or store which produce many types of shoes in Malaysia such as flat, sneakers, wedges, high heels, and leather men shoes. ‘WALK’ focused on producing shoes with affordable price with comfortable wear. ‘WALK’ just want to produce product that can make people keep finding ‘WALK’ to wear shoes. ‘WALK’ will provide as much as good services to customer and make them satisfied with this product. The target market that WALK focus on is men and women. As all know wedges and flats is for women. Women love to have a lot of shoes because women like to make something new like changing style. From that choosing shoes also important to make some style. Sometimes, women also love to see something cute or beautiful and they will buy it. Same goes to shoes, they will look for beautiful shoes and will buy it. This product also focus on stylish person. Style is such a trend nowadays that everyone will follow to satisfied their self. This behavior included all of the stages of ages. People love to spend their money to make themselves style. With WALK they can be stylish with does not need to spend a lot of money. So stylish people will have choice to choose the design that they like. Competitive advantage for ‘WALK’ is the price is affordable with good material. The range price of shoes that ‘WALK’ have offered is between RM50 to RM 200. The price is one of the one thing that customer will refer for. If the price is affordable it can take customer attention the most. By this, hopefully ‘WALK’ will reached the goal to be the affordable branding that customer like.